2010
DOI: 10.1111/j.1471-4159.2010.07021.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in extracellular loop 2 associated with signal transduction in the glycine receptor

Abstract: The glycine receptor (GlyR) is a member of the Cys-loop family of ligand-gated ion channels (LGICs) that includes the nicotinic acetylcholine receptor (nAChR), serotonin type 3 receptor (5-HT 3 R) and GABA type A receptor. Each of these receptors is a pentameric complex, with the subunits arranged around a central ion-conducting pore within the cell membrane (Betz 1990). The individual subunits share a common topology with a large extracellular domain (ECD) at the N-terminus and four transmembrane domain a-hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…6, C-E). Although we initially thought that A52E or A52N might compete with this salt bridge, we found that the 180°o rientation of the side chain of Ala52 versus Glu53 in a ␤ strand was preserved, a result that agrees with recent cysteine substitutions in loop 2 by Cederholm et al (2010). We suggest that these mutations at Ala52 predominantly affect interactions within loop 2 (Fig.…”
Section: Position 52 and Ethanol Sensitivitysupporting
confidence: 80%
See 4 more Smart Citations
“…6, C-E). Although we initially thought that A52E or A52N might compete with this salt bridge, we found that the 180°o rientation of the side chain of Ala52 versus Glu53 in a ␤ strand was preserved, a result that agrees with recent cysteine substitutions in loop 2 by Cederholm et al (2010). We suggest that these mutations at Ala52 predominantly affect interactions within loop 2 (Fig.…”
Section: Position 52 and Ethanol Sensitivitysupporting
confidence: 80%
“…This addition did not alter agonist sensitivity. Prior studies indicate that this lack of effect cannot be attributed to the inaccessibility of MTSES to position 52 (Crawford et al, 2007Cederholm et al, 2010). Moreover, binding a neutral MTS reagent to a cysteine substitution at position 53 did not alter the sensitivity of the mutant receptor to agonist .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations